The Usefulness and Ease of Use Open Office Automation Software Among the Government Staff - Nor Asikin, Ismail (2005)
The purpose of this research is to identify the Malaysian government staff initial perception of the usefulness and ease of use of the open office automation software in their daily work. 30 participants from different faculties in UUM had randomly been selected to evaluate the software. Questionnaire which been adopted from Davis (1989) and Morris and Dillon (1997) was used as data collection instruments. For this study, the participants were presented with a briefly explanation about the OpenOffice.org software then the participants were required to perform several task scenario comprise of the basic functions in document editing. Based on their initial experience with the software, data on the user perception and attitude towards OpenOffice.org software were collected. The findings shows that mostly the administrative staff in UUM have never aware of the OpenOffice.org software before. The results obtained indicate that only 14 percent of the total participants know about the OpenOffice.org. In addition, the results of their perception on the usefulness and ease of use determined that, they were agreed that the software is useful and easy to use. Based on the analysis suggest that both usefulness and ease of use factor has a positive relationship with their attitude towards using the software yet will encourage them to use it in the future.